1991
DOI: 10.1016/s0006-3495(91)82071-9
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared Fourier transform Raman and conventional Raman studies of calf gamma-crystallins in the lyophilized state and in solution

Abstract: We present in this report a detailed structural study of calf gamma-crystallins both in the solid state and in solution by the newly developed technique of near-infrared (IR) Fourier transform (FT)-Raman spectroscopy as well as by the conventional Raman method. In comparison with conventional laser Raman spectroscopy, the near-IR FT-Raman approach exhibits several attractive features such as fluorescence rejection capability, frequency accuracy, and the FT's multiplex and throughput advantages. These distinct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…All three spectra are characterized by the ±SH Raman doublet typical of the g crystallins. This doublet is asymmetrical, with a main band around 2580 cm À1 and a lowerfrequency shoulder near 2560 cm À1 , as reported earlier by us and by others for several bovine g crystallins (Pande et al, 1989(Pande et al, , 1991Chen et al, 1991). While the overall ±SH band pro®les for the three proteins appear to be nearly identical, the area under each pro®le scales exactly with the number of cysteine residues in the corresponding protein.…”
supporting
confidence: 78%
“…All three spectra are characterized by the ±SH Raman doublet typical of the g crystallins. This doublet is asymmetrical, with a main band around 2580 cm À1 and a lowerfrequency shoulder near 2560 cm À1 , as reported earlier by us and by others for several bovine g crystallins (Pande et al, 1989(Pande et al, , 1991Chen et al, 1991). While the overall ±SH band pro®les for the three proteins appear to be nearly identical, the area under each pro®le scales exactly with the number of cysteine residues in the corresponding protein.…”
supporting
confidence: 78%
“…Disulfide bonds play an important role in protein unfolding and assembly. Chen et al 26 reported that Raman spectroscopy was sensitive enough to detect the redox properties of sulfhydryl groups in lens crystallins. As can be seen in Fig.…”
Section: Evaluation Of Conformational Changesmentioning
confidence: 99%
“…Lens proteins may progressly show conspicuous changes during aging and increase water-insoluble protein aggregation as a result of continuous oxidation of the sulfhydryl groups to form disulfide bonds. Spectroscopic studies of eye lens proteins have proved that Raman spectroscopy is capable of detecting directly the formation of disulfide bonds and may serve as a noninvasive tool to monitor lens development ( , ). In this study, the HPLC proteins including high-molecular-weight (HMW) proteins and various crystallins () have been resolved and are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The lens is a lifelong growing organ with no shedding of cellular elements and continuous deposits of the posttranslationally altered proteins in the nucleus and newly synthesized proteins in the cortex. Lens proteins might progressively show conspicuous changes during aging and increase water-insoluble proteins as aggregates resulting from oxidation of sulfhydryl groups to disulfide bonds ( , ). Changes of the sulfhydryl groups could be monitored by Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%